PENGARUH TRANSFORMASI METODE PEMBELAJARAN PAI BERBASIS TRADISI DAN KURIKULUM BERBASIS CINTA TERHADAP MOTIVASI BELAJAR PESERTA DIDIK DI SDIT NURUL IMAN PALEMBANG - Sekar Ardhanun Juwita; Ahmad Zainuri; Mukti Ali (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Islamic Religious Education plays a strategic role in shaping students’ character and personality; however, the use of monotonous traditional teaching methods often leads to low learning motivation. This study aims to determine the effect of transforming traditional IRE teaching methods and implementing a love-based curriculum on students’ learning motivation at SDIT Nurul Iman Palembang. Using a quantitative approach with a Pre-Experimental Design (One-Group Design), this study involved a sample of 34 students. Data were collected via questionnaires and analyzed using classical assumption validity tests as well as hypothesis tests (t-test and F-test) using SPSS software. The results indicate that, individually, the variables of tradition-based methods (X1) and love-based curriculum (X2) have a significant effect on learning motivation (Y1). Simultaneously, both variables also exhibit a significant effect with a significance level of 0.001 < 0.05. The combined effect of the independent variables on learning motivation is 67.4%, as indicated by an Adjusted R-Square value of 0.674. In conclusion, the integration of humanistic and compassion-based curriculum innovations into traditional methods is effective in enhancing student engagement and learning motivation in the modern era.